Chinese associations and associational life in South Africa’s Gauteng Province since the end of apartheid - Pauw, Willem Johann (My University, 2019)
This research focuses on Chinese associations in post-apartheid South Africa. It argues that Chinese associational life during this period has been shaped by the democratic transition in 1994, the emergence of a third wave of Chinese migration, the strengthening of South Africa-China relations and development of new media technologies. The beginnings of Chinese associational life in South Africa date back to the period between the seventeenth and nineteenth centuries; and can be located in the practice of petitioning by Chinese freemen and contracted labourers against colonial oppression. The first formalised Chinese associations emerged in the early 1900s in response to the increasing regulation and anti-Asiatic legislation enacted by British colonialists and thereafter, through Union government rule. The apartheid government exacerbated racial oppression in the second half of the twentieth century and this subsequently led to the centralisation, and shift away from militancy, of Chinese associations under one national organisation. The influx of Taiwanese migrants in the 1980s saw them establishing their own associations – predominantly business orientated – which was made possible by the preferential treatment they received from the apartheid government. Since 1994, these original associations, which draw their membership from the South African-Born Chinese, have transformed to focus predominantly on community and cultural pursuits. This is the result of political shifts and the increasing freedoms guaranteed to all races by democracy, although their membership is declining. Newer associations established by recent Chinese migrants in the democratic era are principally, although not only, business-orientated. This is in the context of new economic opportunities presented by the growing relations between South Africa and China post-1994. Thus, the democratic shift in 1994 transformed SABC associations from being politically orientated towards more social and cultural enterprises; and alternatively, it has allowed for and encouraged the new associations, established by recent Chinese migrants, to have commercial interests. Some of the themes covered in the thesis include associational life, social capital, migration studies, Chinese diasporic studies, Africa/China relations, community, identity, acculturalisation. This project contributes to the growing literature on the history of the Chinese in South Africa; Chinese diasporic communities; associations/associational life; migration studies; Africa-China relations and the impact of social media on migrant networks.
A thesis submitted in fulfilment of the requirements for the degree of Masters in the Department of History, School of Social Sciences, Faculty of Humanities, University of the Witwatersrand. February 2019
Keywords: China--Politics and government; Africa, Sub-Saharan--Politics and government